Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the problem of finding the composition [tex]\((g^{-1} \circ f^{-1})(x)\)[/tex] for the given functions [tex]\( f(x) = e^{2x-1} \)[/tex] and [tex]\( g(x) = 2x-1 \)[/tex], let's follow these steps:
Step 1: Find the inverse of [tex]\( f(x) \)[/tex].
Given:
[tex]\[ f(x) = e^{2x-1} \][/tex]
To find the inverse function [tex]\( f^{-1}(x) \)[/tex]:
1. Start by setting [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = e^{2x-1} \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = e^{2x-1} \][/tex]
Take the natural logarithm on both sides:
[tex]\[ \ln(y) = 2x - 1 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ 2x = \ln(y) + 1 \][/tex]
[tex]\[ x = \frac{\ln(y) + 1}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{\ln(x) + 1}{2} \][/tex]
Step 2: Find the inverse of [tex]\( g(x) \)[/tex].
Given:
[tex]\[ g(x) = 2x - 1 \][/tex]
To find the inverse function [tex]\( g^{-1}(x) \)[/tex]:
1. Set [tex]\( y = g(x) \)[/tex]:
[tex]\[ y = 2x - 1 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x - 1 \][/tex]
[tex]\[ y + 1 = 2x \][/tex]
[tex]\[ x = \frac{y + 1}{2} \][/tex]
Thus, the inverse function [tex]\( g^{-1}(x) \)[/tex] is:
[tex]\[ g^{-1}(x) = \frac{x + 1}{2} \][/tex]
Step 3: Compute the composition [tex]\((g^{-1} \circ f^{-1})(x)\)[/tex].
To find [tex]\((g^{-1} \circ f^{-1})(x)\)[/tex], we need to substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( g^{-1}(x) \)[/tex]:
[tex]\[ (g^{-1} \circ f^{-1})(x) = g^{-1}(f^{-1}(x)) \][/tex]
Substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( g^{-1}(x) \)[/tex]:
[tex]\[ g^{-1}\left( \frac{\ln(x) + 1}{2} \right) = \frac{\frac{\ln(x) + 1}{2} + 1}{2} \][/tex]
Simplify the expression:
[tex]\[ \frac{\frac{\ln(x) + 1}{2} + 1}{2} = \frac{\frac{\ln(x) + 1 + 2}{2}}{2} = \frac{\frac{\ln(x) + 3}{2}}{2} = \frac{\ln(x) + 3}{4} \][/tex]
Thus:
[tex]\[ (g^{-1} \circ f^{-1})(x) = \frac{\ln(x) + 3}{4} \][/tex]
Let's compare this with the given options:
(A) [tex]\(\ln x\)[/tex]
(B) [tex]\(e^x\)[/tex]
(C) [tex]\(\frac{1}{4}(1 + \ln(x)) + \frac{1}{2}\)[/tex]:
[tex]\[ = \frac{1}{4}(1 + \ln(x)) + \frac{1}{2} = \frac{1 + \ln(x)}{4} + \frac{2}{4} = \frac{1 + \ln(x) + 2}{4} = \frac{\ln(x) + 3}{4} \][/tex]
(D) [tex]\(\frac{1}{2}\left(1 + \ln\left(\frac{x + 1}{2}\right)\right)\)[/tex]
Hence, the correct answer is (C):
[tex]\[ \boxed{\frac{1}{4}(1+\ln(x))+\frac{1}{2}} \][/tex]
Step 1: Find the inverse of [tex]\( f(x) \)[/tex].
Given:
[tex]\[ f(x) = e^{2x-1} \][/tex]
To find the inverse function [tex]\( f^{-1}(x) \)[/tex]:
1. Start by setting [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = e^{2x-1} \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = e^{2x-1} \][/tex]
Take the natural logarithm on both sides:
[tex]\[ \ln(y) = 2x - 1 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ 2x = \ln(y) + 1 \][/tex]
[tex]\[ x = \frac{\ln(y) + 1}{2} \][/tex]
Thus, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{\ln(x) + 1}{2} \][/tex]
Step 2: Find the inverse of [tex]\( g(x) \)[/tex].
Given:
[tex]\[ g(x) = 2x - 1 \][/tex]
To find the inverse function [tex]\( g^{-1}(x) \)[/tex]:
1. Set [tex]\( y = g(x) \)[/tex]:
[tex]\[ y = 2x - 1 \][/tex]
2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 2x - 1 \][/tex]
[tex]\[ y + 1 = 2x \][/tex]
[tex]\[ x = \frac{y + 1}{2} \][/tex]
Thus, the inverse function [tex]\( g^{-1}(x) \)[/tex] is:
[tex]\[ g^{-1}(x) = \frac{x + 1}{2} \][/tex]
Step 3: Compute the composition [tex]\((g^{-1} \circ f^{-1})(x)\)[/tex].
To find [tex]\((g^{-1} \circ f^{-1})(x)\)[/tex], we need to substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( g^{-1}(x) \)[/tex]:
[tex]\[ (g^{-1} \circ f^{-1})(x) = g^{-1}(f^{-1}(x)) \][/tex]
Substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( g^{-1}(x) \)[/tex]:
[tex]\[ g^{-1}\left( \frac{\ln(x) + 1}{2} \right) = \frac{\frac{\ln(x) + 1}{2} + 1}{2} \][/tex]
Simplify the expression:
[tex]\[ \frac{\frac{\ln(x) + 1}{2} + 1}{2} = \frac{\frac{\ln(x) + 1 + 2}{2}}{2} = \frac{\frac{\ln(x) + 3}{2}}{2} = \frac{\ln(x) + 3}{4} \][/tex]
Thus:
[tex]\[ (g^{-1} \circ f^{-1})(x) = \frac{\ln(x) + 3}{4} \][/tex]
Let's compare this with the given options:
(A) [tex]\(\ln x\)[/tex]
(B) [tex]\(e^x\)[/tex]
(C) [tex]\(\frac{1}{4}(1 + \ln(x)) + \frac{1}{2}\)[/tex]:
[tex]\[ = \frac{1}{4}(1 + \ln(x)) + \frac{1}{2} = \frac{1 + \ln(x)}{4} + \frac{2}{4} = \frac{1 + \ln(x) + 2}{4} = \frac{\ln(x) + 3}{4} \][/tex]
(D) [tex]\(\frac{1}{2}\left(1 + \ln\left(\frac{x + 1}{2}\right)\right)\)[/tex]
Hence, the correct answer is (C):
[tex]\[ \boxed{\frac{1}{4}(1+\ln(x))+\frac{1}{2}} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.